SnS < 2 > (at) Sn-SA electrode material as well as preparation method and application thereof

The SnS2@Sn-SA electrode material prepared by one-step solvent thermal method solved the volume change and electrochemical performance unstable in lithium-ion batteries by generating SnS2 nanosheet particles and combining them with Sn-SA hydrogel. The problem of high-density energy storage and excellent stable performance are achieved.

CN119419248AActive Publication Date: 2025-02-11NORTHEAST NORMAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411551836.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing tin disulfide materials have problems such as volume changes, low conductivity and capacity attenuation in lithium-ion batteries, resulting in unstable electrochemical performance.

Method used

SnS2@Sn-SA electrode material was prepared by one-step solvothermal method, and SnS2 nanosheet particles were generated in the solvothermal reaction through tetravalent tin salt, sulfur source and sodium alginate, and combined with Sn-SA hydrogel to form a core shell structure.

Benefits of technology

It effectively alleviates the volume changes and agglomeration problems of SnS2, improves the conductivity and lithium ions transmission rate, and achieves high-density energy storage and excellent stable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419248A_ABST
    Figure CN119419248A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery electrode materials, and discloses a SnS < 2 > (at) Sn-SA electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing tetravalent tin salt, a sulfur source, sodium alginate and a solvent by adopting a one-step solvothermal method, so that H2S generated by decomposing the sulfur source in a solvothermal reaction process reacts with Sn < 4 + > in the tetravalent tin salt to generate SnS2 nanosheet particles; and performing chemical crosslinking on Sn < 4 + > in the tetravalent tin salt and carboxyl in the sodium alginate to form Sn-SA hydrogel, thereby obtaining the SnS < 2 >-Sn-SA electrode material which takes the SnS < 2 > nanosheet particles as an inner core and the Sn-SA hydrogel as a shell. The Sn-SA hydrogel of the shell in the SnS < 2 > (at) Sn-SA electrode material prepared by the invention effectively relieves the problems of large volume change, agglomeration and dissolution of SnS < 2 > in the charge-discharge cycle process, and realizes the unification of high-density energy storage and excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for lithium-ion batteries, and specifically relates to a SnS2@Sn-SA electrode material and a preparation method and application thereof. Background Art

[0002] As an energy storage device that combines high energy density and high voltage, lithium-ion batteries have been widely used in portable electronic devices, power tools, hybrid and electric vehicles.

[0003] Graphite is the most widely used carbon-based negative electrode material for lithium-ion batteries. It has high conductivity, excellent interlayer structure and stable electrochemical performance. However, the limitation of lithium storage mechanism on the surface of graphite negative electrode material leads to its low theoretical specific capacity, which is difficult to meet the increasing requirements of high-density energy storage. Therefore, exploring alternatives to carbon-based negative electrode materials is indispensable and challenging.

[0004] Various lithium-ion battery negative electrode materials have been prepared in the prior art, such as metal alloys, metal oxides, metal sulfides, metal phosphides, etc. Among them, layered metal disulfides have a large number of advantageous properties, making them a promising alternative material. The large specific surface area of ​​layered metal disulfides can ensure the optimal contact between active sites and lithium ions, and their adjustable interlayer spacing can also enhance the transmission of lithium ions, thereby reducing the impedance during the electrochemical reaction. Among layered metal disulfides, tin disulfide is unique for its suitable redox potential, high reactivity and high theoretical specific capacity. However, tin disulfide has low intrinsic conductivity, significant volume change during charging and discharging, about 340%, and the tendency of tin disulfide to agglomerate and dissolve in the electrolyte, resulting in obvious capacity decay of tin disulfide, which cannot meet the capacity requirements and exhibits unsatisfactory rate and cycle performance.

[0005] In order to solve the above problems, the existing technology proposes the following solutions: first, by constructing tin disulfide materials with nanostructures, such as nanosheets, nanoparticles and nanoflowers, the effect of the volume change of tin disulfide on the structural stability of lithium-ion batteries can be effectively alleviated, and the diffusion kinetics of lithium ions can be enhanced. Second, by combining tin-based materials with carbonaceous materials, the electronic / ionic conductivity can be improved and the structural collapse caused by the volume change of tin disulfide can be buffered.

[0006] Although the tin disulfide materials prepared by the above methods alleviate the impact of the volume change of tin disulfide on the electrode structure of lithium-ion batteries to a certain extent, the above methods have complicated synthesis procedures, and the prepared tin disulfide still has the problem of poor intrinsic conductivity and unstable electrochemical performance of lithium-ion batteries due to volume change, and cannot effectively solve the problem of electrochemical performance of lithium-ion batteries caused by volume change of tin disulfide. Summary of the invention

[0007] In order to solve the technical problems that the preparation method of the above-mentioned tin disulfide material is complicated and the volume change of tin disulfide affects the electrode structure of lithium-ion batteries, thereby causing unstable electrochemical performance of lithium-ion batteries, the present invention provides a SnS2@Sn-SA electrode material and a preparation method and application. The present invention is prepared using safe and readily available raw materials, and the preparation method is simple. The present invention adopts a one-step solvothermal method to mix a tetravalent tin salt, a sulfur source, sodium alginate and a solvent, so that the sulfur source decomposes during the solvothermal reaction to generate H2S and Sn in the tetravalent tin salt. 4+ Reaction to generate SnS2 nanosheet particles; and Sn in the tetravalent tin salt 4+ The Sn-SA hydrogel is chemically cross-linked with the carboxyl groups in sodium alginate to form a Sn-SA hydrogel, thereby obtaining a SnS2@Sn-SA electrode material with a core-shell structure, with SnS2 nanosheet particles as the core and Sn-SA hydrogel as the shell. The Sn-SA hydrogel in the shell of the SnS2@Sn-SA electrode material prepared by the present invention effectively alleviates the large volume change of the internal SnS2 nanosheet particles, hindering the Sn 4+ The shuttle of SnS2 inhibits the further dissolution and aggregation of SnS2 in organic solvents. This effectively solves the problem of large volume change, aggregation and dissolution of SnS2 during the charge and discharge cycle, and achieves the unity of high-density energy storage and superior stability.

[0008] The first object of the present invention is to provide a method for preparing a SnS2@Sn-SA electrode material, comprising the following steps:

[0009] The tetravalent tin salt, the sulfur source, the sodium alginate and the solvent are mixed to carry out a solvothermal reaction, so that the H2S generated by the decomposition of the sulfur source during the solvothermal reaction reacts with the Sn in the tetravalent tin salt. 4+ Reaction to generate SnS2 nanoparticles; and to make the Sn in the tetravalent tin salt 4+ The Sn-SA hydrogel is formed by chemical cross-linking with the carboxyl and hydroxyl groups in sodium alginate, thereby obtaining the SnS2@Sn-SA electrode material with SnS2 nanosheet particles as the core and Sn-SA hydrogel as the shell.

[0010] It should be noted that in the solvothermal reaction process of the SnS2@Sn-SA electrode material prepared by the present invention, the reaction temperature is the main condition and is the key to ensure the effective synthesis of the active material SnS2. Therefore, by exploring the effect of the solvothermal reaction temperature on the formation and growth of SnS2 nanosheets, the present invention found that the reaction temperature plays a key role in the formation and growth of SnS2 nanosheets. When the temperature is lower than 160°C, the H2S produced by the decomposition of the sulfur source reacts with the Sn in the tetravalent tin salt. 4+The reaction is slow, the growth rate of the generated SnS2 nanosheets is inhibited, and the obtained SnS2 nanoparticles are very few; when the temperature is higher than 200°C, the temperature increase will accelerate the dissolution of part of the generated SnS2, and the growth rate of the SnS2 nanosheets is difficult to control, and the content of active SnS2 in the obtained material is very little. The preferred solvothermal reaction temperature of the present invention is 160°C to 200°C, and the preferred solvothermal reaction time is 10h to 14h.

[0011] In addition, the external Sn-SA hydrogel in the present invention plays a key role in the structure of the internal SnS2 nanoparticles and the transmission performance of lithium ions. If the thickness of the sodium alginate is too thin, that is, the proportion of the sodium alginate is too low, the Sn in the tetravalent tin salt will be 4+ If the Sn-SA hydrogel formed by the cross-linking reaction is too thin, the tolerance of the Sn-SA hydrogel to volume deformation will be affected, which is not conducive to the stability of the structure. If the Sn-SA hydrogel is too thick, it will cause difficulty in lithium ion transmission, resulting in a decrease in lithium ion transmission efficiency. 4+ , the molar ratio of sulfur source to sodium alginate is 1:2~3:0.4~0.8.

[0012] Preferably, the tetravalent tin salt is one of tin tetrachloride pentahydrate and diethyltin dithiocarbamate.

[0013] Preferably, the sulfur source is one of thioacetamide and thiourea.

[0014] Preferably, the solvent is one of isopropanol, water and ethylene glycol.

[0015] The second object of the present invention is to provide SnS2@Sn-SA electrode material prepared by the above preparation method.

[0016] The third object of the present invention is to provide the use of the above-mentioned SnS2@Sn-SA electrode material in the preparation of lithium-ion batteries, wherein the SnS2@Sn-SA electrode material is used as a negative electrode material of the lithium-ion battery.

[0017] Preferably, the method for preparing a lithium ion battery comprises the following steps:

[0018] Preparation of working electrode: Mix SnS2@Sn-SA electrode material, conductive agent and binder, and apply them on copper foil.

[0019] Preparation of electrode sheets: pressing and cutting metallic lithium.

[0020] Preparation of electrolyte: dissolve lithium bis(trifluoromethylsulfonyl)imide in an organic solvent, and add lithium nitrate to prepare an electrolyte.

[0021] Preparation of lithium-ion batteries: The counter electrode plate, diaphragm material, electrolyte and working electrode plate are assembled in sequence to prepare a lithium-ion battery.

[0022] Preferably, the concentration of lithium bis(trifluoromethylsulfonyl)imide in the electrolyte is 1 mol / L, and the content of lithium nitrate is 2.0%.

[0023] Preferably, the organic solvent is ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention mixes a tetravalent tin salt, a sulfur source, sodium alginate and a solvent to perform a solvent thermal reaction, so that during the solvent thermal reaction, H2S generated by the decomposition of the sulfur source reacts with Sn in the tetravalent tin salt. 4+ Reaction to generate SnS2 nanosheet particles; and Sn in the tetravalent tin salt 4+ The Sn-SA hydrogel is chemically cross-linked with the carboxyl and hydroxyl groups in sodium alginate to obtain a SnS2@Sn-SA electrode material having SnS2 nanosheet particles as a core and Sn-SA hydrogel as a shell. The present invention adopts a one-step solvothermal method to prepare the SnS2@Sn-SA electrode material. The preparation method of the present invention is simple and the raw materials used are safe and easily available.

[0026] The SnS2@Sn-SA electrode material prepared by the present invention is prepared by reacting Sn in the tetravalent tin salt in a solvent thermal reaction process. 4+ Chemical cross-linking with carboxyl and hydroxyl groups in sodium alginate forms Sn-SA hydrogel as the shell of SnS2@Sn-SA electrode material. Since the formed Sn-SA hydrogel has a viscous and elastic gel-like structure, it effectively alleviates the volume change of SnS2 during the cycle, inhibits the further dissolution of SnS2 in organic solvents, and also hinders the agglomeration of SnS2, thus effectively solving the problem of large volume change, agglomeration and dissolution of SnS2 during the charge and discharge cycle.

[0027] The SnS2@Sn-SA electrode material prepared by the present invention reacts H2S generated by decomposition of the sulfur source in the solvent thermal reaction with Sn in the tetravalent tin salt. 4+ The SnS2 nanosheet particles are formed by the reaction, and the SnS2@Sn-SA electrode material is used as the core. The present invention synthesizes thinner SnS2 nanosheet particles, and the Sn-SA hydrogel contains more Sn 4+ Ions, large amounts of Sn 4+ The ions are coated on the surface of SnS2 as a protective layer of SnS2, which improves the conductivity of the SnS2 composite material and increases the Li +The transmission rate is improved, which overcomes the problem of poor conductivity of SnS2, significantly reduces the resistance between the composite material and the electrolyte, and realizes the unity of high-density energy storage and excellent stability of SnS2. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the preparation principle of the SnS2@Sn-SA electrode material of the present invention.

[0029] Figure 2 XRD characterization diagrams of the SnS2@Sn-SA electrode material in Example 1 of the present invention, the SnS2@SA electrode material in Comparative Example 1, and the SnS2 electrode material in Comparative Example 2.

[0030] Figure 3 The Raman spectra of the SnS2@Sn-SA electrode material in Example 1 of the present invention, the SnS2@SA electrode material in Comparative Example 1, and the SnS2 electrode material in Comparative Example 2 are shown in FIG. Figure 3 The illustrations in Figure 3 Medium 1000cm -1 ~2000cm -1 A magnified view of the range.

[0031] Figure 4 This is a thermogravimetric analysis characterization diagram of the SnS2@Sn-SA electrode material in Example 1 of the present invention and the SnS2@SA electrode material in Comparative Example 1.

[0032] Figure 5 Figure 2 is the transmission electron microscope image of the SnS2@Sn-SA electrode material in Example 1 of the present invention at different magnifications; wherein, Figure a is a transmission electron microscope image at 200nm, Figure b is a transmission electron microscope image at 50nm, Figure c is a transmission electron microscope image at 20nm, Figure d is a transmission electron microscope surface scan of the SnS2@Sn-SA electrode material in Example 1 at 500nm, Figure e is the Sn element distribution diagram in Figure d, Figure f is the S element distribution diagram in Figure d, and Figure g is the C element distribution diagram in Figure d.

[0033] Figure 6 This is the cyclic voltammetry curve of the SnS2@Sn-SA electrode material in Example 1 of the present invention.

[0034] Figure 7 This is a constant current charge and discharge curve of the SnS2@Sn-SA electrode material in Example 1 of the present invention.

[0035] Figure 8 Graph showing the charge / discharge capacity of the SnS2@Sn-SA electrode material at different current densities in Example 1 of the present invention.

[0036] Fig. 9It is the impedance data of the SnS2@Sn-SA electrode material in Example 1 of the present invention; wherein, Figure a is the AC impedance spectrum of the SnS2@Sn-SA electrode material in Example 1, the illustration in Figure a is an enlarged view of Figure a in the high-frequency region, and Figure b is an equivalent circuit diagram of the AC impedance of Figure a.

[0037] Fig.10 This is a test diagram of the cycle stability of the SnS2@Sn-SA electrode material at 1C in Example 1 of the present invention.

[0038] Fig.11 It is a capacitance contribution calculation diagram of the SnS2@Sn-SA electrode material in Example 1 of the present invention; wherein, Figure a is a cyclic voltammogram of the SnS2@Sn-SA electrode material in Example 1, Figure b is a capacitance storage contribution diagram of the SnS2@Sn-SA electrode material in Example 1, and Figure c is a capacitance contribution diagram of the SnS2@Sn-SA electrode material in Example 1 at different scanning rates.

[0039] Fig.12 This is a capacity comparison chart of the SnS2@Sn-SA electrode material in Example 1 of the present invention and that reported in existing literature. DETAILED DESCRIPTION

[0040] In order to enable those skilled in the art to better understand that the technical solution of the present invention can be implemented, the present invention is further described below in conjunction with specific embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.

[0042] The invention is further described below through specific examples.

[0043] Example 1

[0044] This embodiment provides a method for preparing a SnS2@Sn-SA electrode material.

[0045] Dissolve 0.36g of tin tetrachloride pentahydrate, 0.21g of thioacetamide and 0.1g of sodium alginate in 20mL of water, stir at room temperature for 30min, stir evenly, and perform solvothermal reaction at 180℃ in a high pressure reactor for 12h. After the solvothermal reaction is completed, take out the solid powder, rinse it with deionized water and anhydrous ethanol in turn, and then dry it in a vacuum drying oven at 60℃ for 8h to obtain SnS2@Sn-SA electrode material.

[0046] Example 2

[0047] This embodiment provides a method for preparing a SnS2@Sn-SA electrode material.

[0048] 0.36 g of tin tetrachloride pentahydrate, 0.21 g of thioacetamide and 0.15 g of sodium alginate were dissolved in 20 mL of isopropanol and stirred at room temperature for 30 min. After stirring evenly, the mixture was subjected to solvent thermal reaction at 160 °C in a high pressure reactor for 10 h. After the solvent thermal reaction was completed, the solid powder was taken out and rinsed with deionized water and anhydrous ethanol in turn, and then dried in a vacuum drying oven at 60 °C for 8 h to obtain SnS2@Sn-SA electrode material.

[0049] The difference between this embodiment and embodiment 1 is that the temperature of the solvent thermal reaction is 160° C. and the time is 10 h.

[0050] Example 3

[0051] This embodiment provides a method for preparing a SnS2@Sn-SA electrode material.

[0052] 0.36 g of tin tetrachloride pentahydrate, 0.21 g of thioacetamide, and 0.09 g of sodium alginate were dissolved in 20 mL of isopropanol and stirred at room temperature for 30 min. After stirring evenly, the mixture was subjected to solvent thermal reaction at 200 °C in a high-pressure reactor for 14 h. After the solvent thermal reaction was completed, the solid powder was taken out, rinsed with deionized water and anhydrous ethanol in turn, and then dried in a vacuum drying oven at 60 °C for 8 h to obtain SnS2@Sn-SA electrode material.

[0053] The difference between this embodiment and embodiment 1 is that the temperature of the solvent thermal reaction is 200° C. and the time is 14 h.

[0054] Example 4

[0055] This embodiment provides a method for preparing a SnS2@Sn-SA electrode material.

[0056] 0.36 g of diethyl dithiocarbamate, 0.21 g of thioacetamide and 0.1 g of sodium alginate were dissolved in 20 mL of isopropanol and stirred at room temperature for 30 min. After stirring evenly, the mixture was subjected to solvent thermal reaction at 160 °C in a high pressure reactor for 10 h. After the solvent thermal reaction was completed, the solid powder was taken out and rinsed with deionized water and anhydrous ethanol in turn, and then dried in a vacuum drying oven at 60 °C for 8 h to obtain SnS2@Sn-SA electrode material.

[0057] The difference between this embodiment and embodiment 1 is that the sulfur source is thioacetamide.

[0058] Example 5

[0059] This embodiment provides a method for preparing a SnS2@Sn-SA electrode material.

[0060] Dissolve 0.36g of tin tetrachloride pentahydrate, 0.21g of thiourea and 0.1g of sodium alginate in 20mL of water, stir at room temperature for 30min, stir evenly, and perform solvothermal reaction at 180℃ in a high pressure reactor for 12h. After the solvothermal reaction is completed, take out the solid powder, rinse it with deionized water and anhydrous ethanol in turn, and then dry it in a vacuum drying oven at 60℃ for 8h to obtain SnS2@Sn-SA electrode material.

[0061] The difference between this embodiment and embodiment 1 is that the tin source is tin diethyldithiocarbamate.

[0062] Example 6

[0063] This embodiment provides a method for preparing a lithium ion battery.

[0064] Preparation of working electrode pole piece: The SnS2@Sn-SA electrode material of Example 1, polyvinylidene fluoride and acetylene black are uniformly mixed in a mass ratio of 80:10:10, dissolved in N-methylpyrrolidone, and the slurry is uniformly applied on a 15 μm thick copper foil and dried.

[0065] Preparation of electrode plates: metallic lithium is pressed and cut into 0.6 cm discs.

[0066] Preparation of electrolyte: 28.71 g of lithium bis(trifluoromethylsulfonyl)imide was dissolved in 100 mL of an organic solvent, and 2.0 g of lithium nitrate was added, wherein the organic solvent was ethylene glycol dimethyl ether and 1,3-dioxolane, and the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane was 1:1.

[0067] Preparation of lithium-ion battery: copper foil was cut into discs with a radius of 0.6 cm as the working electrode, lithium foil was used as the counter electrode, Cellgard 2400 separator and electrolyte were assembled in a glove box filled with argon (O2 and H2O <1ppm) to assemble CR2025 button cells.

[0068] Comparative Example 1

[0069] This comparative example provides a method for preparing a SnS2@SA electrode material.

[0070] S1. Dissolve 0.36g of tin tetrachloride pentahydrate and 0.21g of thioacetamide in 20mL of isopropanol, stir at room temperature for 30min, stir evenly, and perform solvent thermal reaction at 180°C in a high pressure reactor for 12h. After the solvent thermal reaction is completed, take out the solid powder, rinse it with deionized water and anhydrous ethanol in turn, and then dry it in a vacuum drying oven at 60°C for 8h to obtain SnS2 electrode material;

[0071] S2. Soak 0.3 g of SnS2 prepared from the above S1 in 25 mL of an aqueous solution containing 0.125 g of sodium alginate for 4 h, then centrifuge the solid, rinse it with deionized water and anhydrous ethanol in turn, and then dry it in a vacuum drying oven at 60°C for 8 h to obtain SnS2@SA electrode material.

[0072] The difference between Comparative Example 1 and Example 1 is that the SnS2 electrode material is first synthesized by a solvothermal method, and then the SnS2 electrode material is mixed with a sodium alginate aqueous solution to obtain a SnS2@SA electrode material.

[0073] Comparative Example 2

[0074] This comparative example provides a method for preparing a SnS2 electrode material.

[0075] Dissolve 0.36 g of tin tetrachloride pentahydrate and 0.21 g of thioacetamide in 20 mL of isopropanol, stir at room temperature for 30 min, and after stirring evenly, perform solvent thermal reaction at 180 °C in a high-pressure reactor for 12 h. After the solvent thermal reaction is completed, take out the solid powder, rinse it with deionized water and anhydrous ethanol in turn, and then dry it in a vacuum drying oven at 60 °C for 8 h to obtain SnS2 electrode material.

[0076] The difference between Comparative Example 2 and Example 1 is that the SnS2 electrode material is synthesized by only the solvothermal method without mixing with the sodium alginate aqueous solution.

[0077] Experimental Section

[0078] Examples 1 to 3 of the present invention all prepare SnS2@Sn-SA electrode materials that solve the problems of large volume change, agglomeration and dissolution of SnS2 during the charge and discharge cycle. The following is a study using the SnS2@Sn-SA electrode materials prepared in Example 1 and Comparative Examples 1 to 2 as examples. The specific research methods and results are as follows:

[0079] 1. Material Characterization

[0080] Figure 1 This is a schematic diagram of the preparation principle of the SnS2@Sn-SA electrode material of the present invention.

[0081] Figure 2 Figure 1 is an XRD characterization diagram of the SnS2@Sn-SA electrode material in Example 1, the SnS2@SA electrode material in Comparative Example 1, and the SnS2 electrode material in Comparative Example 2. Figure 2 As shown, the sharp characteristic peaks at 2θ=14.86°, 28.22°, 32.08° and 49.99° can correspond to the (001), (100), (101) and (110) crystal planes of SnS2, indicating that the present invention obtains SnS2 crystals by a one-step hot solvent method.

[0082] Figure 3 The Raman spectra of the SnS2@Sn-SA electrode material in Example 1, the SnS2@SA electrode material in Comparative Example 1, and the SnS2 electrode material in Comparative Example 2 are shown in FIG. Figure 3 As shown, at 311cm -1 There is a strong Raman characteristic peak at A 1g Mode, at 1350cm -1 ~1580cm -1 A broad characteristic peak of SA organic structure was observed, which fully confirmed the successful synthesis of SnS2@Sn-SA electrode material.

[0083] Figure 4 Thermogravimetric analysis diagrams of the SnS2@Sn-SA electrode material in Example 1 and the SnS2@SA electrode material in Comparative Example 1. Figure 4 It can be seen that the slow decrease in mass before 400°C corresponds to the loss of water molecules in sodium alginate, and the rapid decrease in weight between 400°C and 430°C is attributed to the decomposition of sodium alginate molecules. It can be calculated that the mass proportions of SnS2 in Example 1 and Comparative Example 1 are 78.67% and 79.27%, respectively.

[0084] Figure 5 Figure 1 is a transmission electron microscope characterization diagram of the SnS2@Sn-SA electrode material in Example 1 at different magnifications; Figure a is a morphology diagram at 200nm, Figure b is a morphology diagram at 50nm, Figure c is a morphology diagram at 20nm, Figure d is an element test diagram, Figure e is a Sn element analysis diagram, Figure f is a S element analysis diagram, and Figure g is a C element analysis diagram. Figure 5 Figure a, Figure 5 Figure b and Figure 5 As can be seen in Figure c, SnS2 shows a two-dimensional nanosheet morphology. A hydrogel protective layer Sn-SA is observed on the surface of SnS2, with an interlayer spacing of ~0.59 nm, which can correspond to the (001) lattice plane of SnS2. Such a large interlayer spacing can ensure the Li +The absence of any distinct lattice planes in the Sn-SA layer confirms its amorphous nature, which is consistent with Figure 1 The XRD results are very consistent. Figure 5 As shown in Figures d to g, it can be clearly observed that the Sn, S and C elements are concentrated on the central nanoparticles, confirming the existence of SnS2 in the electrode material and proving that the Sn-SA layer is uniformly distributed on the surface of the SnS2 nanosheets.

[0085] 2. Electrochemical performance test:

[0086] The battery was electrochemically tested. When performing cyclic voltammetry scanning, the range of the cyclic voltammetry characteristic curve was 0.01V to 3V, and the scanning rate was 0.2mV s -1 ~1mV s -1 . When performing constant current charge and discharge tests, the voltage range is set to 0.01V~3V, and the current intensity is 10μA~640μA. When performing impedance tests, the frequency range is set to 100kHz~10mHz, and the voltage amplitude is 10mV. When performing cycle stability tests using constant current charge and discharge, the voltage range is set to 0.01V~3V, the current density is set to 1C, and the number of cycles is 1000 times.

[0087] The electrochemical performance of SnS2@Sn-SA electrode material was studied by assembling coin-type lithium-ion batteries with the electrode material of Example 1 as the working electrode and lithium foil as the counter electrode and reference electrode. -1 The first four cycles of cyclic voltammetry curves are as follows Figure 6 As shown in the figure, during the first discharge cycle, two obvious reduction peaks appeared at ~1.87V and ~1.17V, corresponding to the lithiation reaction peaks of SnS2. 4+ Reduced to Sn 0 , the reaction formula is SnS2+xLi + +xe - →Li x SnS2 and Li x SnS2+(4-x)Li + +4e - →Sn+2Li2S, the reduction peak at ~0.53V corresponds to the formation of Li-Sn alloy, the reaction formula is During the first cycle of charging, an obvious oxidation peak appeared at ~0.53V, which can correspond to the delithiation of Li-Sn alloy to form Sn. Compared with the electrode materials coated with SA in Example 1 and Comparative Example 1, the SnS2 prepared in Comparative Example 2 showed a small oxidation peak at ~1.47V, indicating that the introduction of SA promoted the reaction kinetics of SnS2. With the increase of the number of scanning cycles, during the 2-4 cycle discharge process, the cyclic voltammetry curves of the SnS2@Sn-SA electrode material with a cross-linked protective Sn-SA layer overlapped rapidly in the subsequent cycles, while the cyclic voltammetry curves of the SnS2 prepared in Comparative Example 1 and the SnS2@SA prepared in Comparative Example 2 continued to decay. The comparison shows that SnS2@Sn-SA has superior reversibility and structural stability given by the combination of cross-linked protective Sn-SA layers.

[0088] Figure 7 The constant current charge-discharge curve of the SnS2@Sn-SA electrode material in Example 1 is shown in FIG. Figure 7 As shown in Figure 1, the charge and discharge capacity of the SnS2@Sn-SA electrode material of Example 1 is stable at 875 mAh g -1 and 939mAh g -1 Thanks to the protection of the Sn-SA layer in the SnS2@Sn-SA electrode material structure, the structural fragmentation caused by the volume change of SnS2 nanosheet particles during the cycle process can be effectively alleviated, and the SnS2@Sn-SA electrode material has excellent redox reversibility.

[0089] Figure 8 Figure 2 is the charge / discharge capacity diagram of the SnS2@Sn-SA electrode material in Example 1 at different current densities. Figure 8 It can be seen that the SnS2@Sn-SA electrode material has excellent rate performance and can achieve deep charge and discharge at high current density.

[0090] Fig. 9 The impedance data of SnS2@Sn-SA electrode material in Example 1; Figure a is the AC impedance spectrum, the inset is the enlarged view of the high-frequency region, and Figure b is the equivalent circuit diagram for fitting the AC impedance. Fig. 9 As shown in Figure a, the impedance spectrum shows that the intrinsic resistance of the SnS2@Sn-SA electrode material is ~1.25Ω before cycling and ~2.26Ω after cycling. The lower resistance is conducive to the transmission of electrons and ions and improves the utilization rate of SnS2. The resistance changes little before and after cycling, indicating that the structure of the SnS2@Sn-SA electrode material is stable.

[0091] Fig.10The cycle stability test diagram of the SnS2@Sn-SA electrode material at 1C in Example 1 is shown in FIG. The cycle stability of the SnS2@Sn-SA electrode material is further verified by long-term charge and discharge. Fig.10 As shown in Figure 2, after 1000 cycles, the capacity remains at 223 mAh g -1 , showing excellent lithium storage capacity and outstanding cycle stability. During the entire cycle, the Coulombic efficiency of the SnS2@Sn-SA electrode material remained at a level close to 100%.

[0092] Fig.11 Figure 1 is a capacitance contribution calculation diagram of the SnS2@Sn-SA electrode material in Example 1; Figure a is a cyclic voltammetry curve of the SnS2@Sn-SA electrode material in Example 1, Figure b is a capacitance storage contribution diagram of the SnS2@Sn-SA electrode material in Example 1, and Figure c is a capacitance contribution diagram of the SnS2@Sn-SA electrode material in Example 1 at different scan rates. Fig.11 As shown, by studying the capacitance contribution of SnS2@Sn-SA electrode material, the utilization rate of SnS2 in SnS2@Sn-SA electrode material was further calculated to be ~57.5%.

[0093] Fig.12 Figure 1 is a comparison chart of the capacity of the SnS2@Sn-SA electrode material in Example 1 and that reported in existing literature. Fig.12 As shown, compared with other SnS2-based electrode materials in the prior art, the SnS2@Sn-SA electrode material of the present invention has excellent capacity. The references corresponding to the samples in the figure are shown in Table 1:

[0094] Table 1 References

[0095] Electrode Materials References capacity <![CDATA[SnS2@SWCNTs]]> doi:0.1021 / acs.nanolett.4c01641 <![CDATA[520(0.2A g -1 )]]> SnS2 / HGF doi:0.1007 / s40820-022-00914-5 <![CDATA[510(0.1A g -1 )]]> <![CDATA[SnS2@C / CNF]]> doi:10.1002 / smtd.202101484 <![CDATA[788(0.5A g -1 )]]> <![CDATA[SnS2-MoS2]]> doi:10.34133 / 2022 / 9846797 <![CDATA[482(0.1A g -1 )]]> <![CDATA[HPC-SnS2-PAN-500]]> doi:10.1016 / j.jmst.2020.12.068 <![CDATA[663.7(0.5A g -1 ) <!-- 7 -->]]> S-TC-2 doi:10.1016 / j.cej.2019.122590 <![CDATA[540.4(0.2A g -1 )]]> H-TiO2@SnS2@PPy doi:10.1002 / anie.201811784 <![CDATA[702.5(0.2A g -1 )]]> Sb2S3-SnS2 doi:10.1016 / j.ensm.2018.10.002 <![CDATA[661(0.5A g -1 )]]> <![CDATA[SnO2@SnS2@NG]]> doi:10.1016 / j.ensm.2018.11.024 <![CDATA[715(0.5A g -1 )]]> <![CDATA[SnS2@CNT]]> doi:10.1021 / acsnano.8b02861 <![CDATA[740(0.1A g -1 )]]> <![CDATA[Sn 0.91 What 0.19 S2]]> doi:10.1002 / smll.201702184 <![CDATA[766.8(0.2A g -1 )]]>

[0096] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing SnS2@Sn-SA electrode material, characterized in that: The following steps are involved: The tetravalent tin salt, the sulfur source, the sodium alginate and the solvent are mixed to carry out a solvothermal reaction, so that the H2S generated by the decomposition of the sulfur source during the solvothermal reaction reacts with the Sn in the tetravalent tin salt. 4+ Reaction to generate SnS2 nanosheet particles; and Sn in the tetravalent tin salt 4+ Chemical cross-linking with the carboxyl and hydroxyl groups in sodium alginate forms Sn-SA hydrogel, thereby obtaining SnS2@Sn-SA electrode material with SnS2 nanosheet particles as the core and Sn-SA hydrogel as the shell.

2. The method for preparing the SnS2@Sn-SA electrode material according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 160°C to 200°C.

3. The method for preparing the SnS2@Sn-SA electrode material according to claim 1, characterized in that: The solvent thermal reaction time is 10h to 14h.

4. The method for preparing the SnS2@Sn-SA electrode material according to claim 1, characterized in that: The Sn in the tetravalent tin salt 4+ , the molar ratio of sulfur source to sodium alginate is 1:2~3:0.4~0.

8.

5. The method for preparing the SnS2@Sn-SA electrode material according to claim 1, characterized in that: The tetravalent tin salt is one of tin tetrachloride pentahydrate and diethyltin dithiocarbamate.

6. The method for preparing the SnS2@Sn-SA electrode material according to claim 1, characterized in that: The sulfur source is one of thioacetamide and thiourea.

7. The method for preparing the SnS2@Sn-SA electrode material according to claim 1, characterized in that: The solvent is one of isopropanol, water and ethylene glycol.

8. A SnS2@Sn-SA electrode material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the SnS2@Sn-SA electrode material according to claim 8 in negative electrode materials for lithium-ion batteries.

10. The use according to claim 9, characterized in that: The preparation of the lithium ion battery comprises the following steps: Preparation of working electrode: Mix SnS2@Sn-SA electrode material, conductive agent and binder, and apply them on copper foil; Preparation of electrode sheets: pressing and cutting the metallic lithium; Preparation of electrolyte: dissolving lithium bis(trifluoromethylsulfonyl)imide in an organic solvent and adding lithium nitrate to prepare an electrolyte; Preparation of lithium-ion batteries: The counter electrode, diaphragm material, electrolyte and working electrode are assembled in sequence to prepare lithium-ion batteries.

Citation Information

Patent Citations

  • Preparation method of SnS2 nanoplate anode material of a lithium-ion battery

    CN101609887A

  • Preparation method of SnS2 / CNTs composite nano material and application of SnS2 / CNTs composite nano material to sodium ion battery negative electrode material

    CN106099064A

  • Method for preparing SnS2 hexagonal nanosheets by hydrothermal process

    CN106830056A